Didactical analysis and planning of school tasks in preservice mathematics teacher training (2002)
In this paper, we propose the didactical analysis as a tool to assist future secondary mathematics teachers in their analysis of mathematics content in order to plan, implement, and assess teaching and learning tasks in class. We propose a conceptual structure that supports the curriculum design of a methods course and present the elements composing the didactical knowledge that we expect preservice teachers to develop in such course.